Optimization of Selling Price Determination through Calculation of Cost of Goods Manufactured and Overhead Costs at Angliss Bakery - Purnama Sari; Ratih Amelia (SEAN Institute, 2026)
This study analyzes the effect of Cost of Goods Manufactured (COGM) calculation and production overhead costs on selling price determination at Angliss Bakery in Medan City. One of the main problems faced by micro, small, and medium enterprises (MSMEs) such as Angliss Bakery is the lack of an optimal cost accounting system, resulting in selling prices that are often determined in a simple manner and tend to rely on intuition. This condition may lead to a mismatch between the selling price and the actual production cost, which can affect the effectiveness of business management. This research employs a quantitative method with a causal associative approach. Data were collected through observation, interviews, and documentation, covering components of raw material costs, direct labor costs, production overhead costs, and selling prices for ten types of bakery products. The data analysis techniques include classical assumption tests, multiple linear regression, partial tests (t-test), simultaneous tests (F-test), and the coefficient of determination (R²) to measure the effect of each independent variable on the dependent variable. The results indicate that the calculation of COGM has a significant effect on the selling price determination of Angliss Bakery products. Production overhead costs also have a significant effect, although their contribution is relatively smaller than that of COGM. Simultaneously, both variables have a positive effect on selling price determination, meaning that the more accurate the COGM calculation and overhead cost allocation, the more accurate the selling price established by the business. Therefore, this study highlights the importance of implementing a more structured cost accounting system in MSME management, particularly in calculating COGM and allocating production overhead costs. These findings are expected to provide useful input for Angliss Bakery in enhancing its competitiveness through a rational pricing strategy based on accurate cost data.